EFFECT OF PHOSPHORUS LEVELS AND PSB ON GROWTH INDICES AND YIELD OF GREEN GRAM [VIGNA RADIATA (L.) WILCZEK] UNDER CUSTARD APPLE (ANNONA SQUAMOSA) BASED ON AGRIHORTI SYSTEM - JAIVEER SINGH DHEWA,; YASHWANT SINGH,; SULOCHANA,; R. BAJIA, (The Bioscan, 2015)
A field experiment was conducted during Kharif season of 2011-12 at the Instructional Farm, Rajiv Gandhi South Campus, Banaras Hindu University, Barkachha, Mirzapur to evaluate the “effect of phosphorus levels and PSB on growth indices and yield of green gram [Vigna radiata (L) Wilczek] under Custard apple (Annona squamosa) based on agri-horti system”. Treatments consisted of green gram Control, 20, 30, 40 Kg P205 ha-1, PSB (S1)+20, 30, 40Kg P2O5 ha-1, PSB (S2)+20,30, 40 Kg P2O5 ha-1, PSB(S1)+PSB(S2)+20, 30, 40 Kg P2O5 ha-1 during Kharif 2011-12. The mean maximum plant height, dry matter accumulation and number of trifoliate leaves of green gram under dual inoculation of PSB (S1) + PSB (S2) along with 40 kg P2O5 ha-1 at all successive stage which were significantly superior to control, 20 kg P2O5 ha-1 and 30 kg P2O5 ha-1 during the experimentation. The seed inoculation with PSB (S1) + PSB (S2) under the application of 40 kg P2O5 ha-1 + PSB (S1) + PSB (S2) recorded the maximum grain yield at par with 40 kg P2O5 ha-1 either under PSB (S2), 40 kg P2O5 ha-1 + PSB (S1) and 30 kg P2O5 ha-1 + PSB (S1) + PSB (S2) significantly superior over rest of treatment.